Sentiment Analysis Website Interface Improvements to Enhance User Experience - Gotra, Anak Agung Ngurah Mahadana Apta; Karyawati, Anak Agung Istri Ngurah Eka; Suhartana, I Ketut Gede; Putra, I Gusti Ngurah Anom Cahyadi (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2025)
Good interface design is very important to improve user experience, especially in web applications. This research aims to redesign the interface of the website loremipsum.com using the User Centered Design (UCD) method to overcome the problems identified through heuristic evaluation. The design process includes four main stages of UCD, namely understanding the context of use, specifying user requirements, designing solutions, evaluating against requirements. All identified issues was implemented, such as responsive design, dark mode, character counter, and CSV file upload capability for large-scale data analysis. A design evaluation was conducted using the System Usability Scale (SUS) with a score of 73, indicating a good level of usability. In addition, the Naive Bayes algorithm was used for sentiment analysis, achieving 73% accuracy. The results show that this redesign not only improves the usability of the website, but also provides a better user experience and efficiently supports the needs of sentiment analysis.